Automatic replenishment of perishables in grocery retailing: The value of utilizing remaining shelf life information. Issue 9 (3rd September 2018) - Kiil, Kasper; Hvolby, Hans-Henrik; Fraser, Kym; Dreyer, Heidi; Strandhagen, Jan Ola
Abstract : Purpose: The purpose of this paper is to investigate the impact of sharing and utilizing remaining shelf life (RSL) information from grocery stores by the use of age-based replenishment policies for perishables. Design/methodology/approach: The performance is evaluated through a discrete event simulation model, which mirrors a part of one of Norway's largest grocery retailer and uses their POS data to reflect a realistic demand pattern of 232 stores for one year. Findings: The findings indicate that a current age-based replenishment policy (EWA policy) provides a significant improvement of 17.7 percent increase in availability for perishables with a shelf life between 4 and 11 days, but suffers from high inventory levels and only reduces waste by 3.4 percent compared to a base stock policy. A proposed adjustment to the EWA policy, EWASS, provides a more balanced performance in the conducted study with a reduction of 10.7 percent waste and 10.3 percent increase in availability by keeping the same average inventory level. Practical implications: Sharing and utilizing RSL information for replenishment of perishables with a predetermined shelf life between 6 and 11 days can be beneficial, and could enable the replenishment processes to be automated. However, for products with longer shelf life, the benefits slowly diminish. Originality/value: The study proposes a new age-based replenishment policy which in the conducted study showed a more balanced performance improvement, in both waste and availability, compared with previous replenishment policies.